A comparative study of propofol and N2O versus sevoflurane and N2O with respect to haemodynamic response and ease of laryngeal mask airway insertion: a prospective randomized double blinded study - Mathur, Veena; Garg, Deepak; Jain, Neena; Singhal, Vivek; Khare, Arvind; Sethi, Surendra K. (International Journal of Research in Medical Sciences, 2017)
Background: Laryngeal mask airway (LMA) is an accepted airway device for spontaneous and modest positive pressure ventilation. Propofol is widely used Induction agent. Sevoflurane is a newer pleasant volatile anaesthetic with rapid induction and recovery with stable haemodynamics. The aim of this study was to compare propofol and sevoflurane with respect of haemodynamic changes and conditions for LMA insertion. Methods: This study was done on 60 female patients of ASA I, II grade between 20-60 years of age. Patients were randomized into two groups (n=30). All patients were preoxygenated and received inj. fentanyl 2µg/kg. Induction agent was propofol 2.5mg/kg (group P) or sevoflurane 8% with vital capacity breath (group S). Loss of eyelash reflex was the end point of induction. Induction time, conditions for LMA insertion, number of attempts, time of successful LMA insertion and haemodynamic parameters were noted. Results: time for induction and LMA insertion was significantly faster in propofol group than group S (p<0.05). Successful LMA insertion in first attempt was 100% in group P with excellent conditions (score 18) while in group S, it was 86.7% with excellent to satisfactory conditions (score 16-17). A significant fall in mean arterial pressure (p<0.05) was noted in group P while pulse rates were comparable in both groups. Conclusions: Sevoflurane vital capacity breath inhalational induction can be used as an effective alternative to propofol though it requires greater time for LMA insertion but with better haemodynamic stability.